AKT/mTOR/BDNF pathway mediates the antidepressant-like effects of NAc-DBS in a mouse model of depression - Li, Ranran; Huang, Xuhui; Lv, Siwen; Liu, Yongtao; Li, Ruijiao; Li, Qianqian; Zhu, Junyao; Ren, Wenjie; Geng, Lujing; Ma, Shuangping; Yu, Yi; Wang, Lei; et al. (Frontiers in Behavioral Neuroscience, 2025)
Deep brain stimulation of the nucleus accumbens (NAc-DBS) has been shown to ameliorate depressive-like behaviors. However, the underlying mechanisms of action remain elusive. We aimed to investigate the impact of NAc-DBS on synaptic spine alterations in hippocampus in a depression mice model and unveil the possible signal pathway mediating such effects. The experimental protocol involved exposing adult mice to chronic unpredictable mild stress (CUMS) with or without NAc-DBS. Behavioral assessments were performed to evaluate the impact of NAc-DBS on emotional alterations. Local field potential (LFP) recordings were employed to examine the hippocampal neuronal activity in awake mice. Golgi-Cox staining was applied to quantify modifications in dendritic spine density. Additionally, hippocampal protein expression of postsynaptic density protein-95 (PSD-95), brain-derived neurotrophic factor (BDNF), and the protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling pathway were analyzed. Results indicate that CUMS mice exhibited apparent depressive-like behaviors, concomitant with reduced hippocampal high gamma oscillation power and synaptic spine density. In addition, CUMS reduced the expression level of PSD-95 and BDNF in mice hippocampus, as well as phosphorylated AKT and mTOR protein. The study revealed that NAc-DBS could attenuate depression-like behaviors, restore high gamma oscillation power and enhance synaptic spine density, potentially by increasing BDNF protein expression level and activating AKT/mTOR signaling pathway. Furthermore, Rapamycin, a potent and specific mTOR inhibitor, was found to moderate the effects of NAc-DBS. These findings suggest that NAc-DBS could enhance synaptic spine density via AKT/mTOR/BDNF signal pathway, which may partially underline its potential antidepressant effects in CUMS induced depressive models.